Human Bone Marrow-Derived Myeloid Dendritic Cells Show an Immature Transcriptional and Functional Profile Compared to Their Peripheral Blood Counterparts and Separate from Slan+ Non-Classical Monocytes - van Leeuwen-Kerkhoff, Nathalie; Lundberg, Kristina; Westers, Theresia M.; Kordasti, Shahram; Bontkes, Hetty J.; Lindstedt, Malin; de Gruijl, Tanja D.; van de Loosdrecht, Arjan A. (Frontiers in Immunology, 2018)
The human bone marrow (BM) gives rise to all distinct blood cell lineages, including CD1c+ and CD141+ myeloid dendritic cells (DC) and monocytes. These cell subsets are also present in peripheral blood (PB) and lymphoid tissues. However, the difference between the BM and PB compartment in terms of differentiation state and immunological role of DC is not yet known. The BM may represent both a site for development as well as a possible effector site and so far, little is known in this light with respect to different DC subsets. Using genome-wide transcriptional profiling we found clear differences between the BM and PB compartment and a location-dependent clustering for CD1c+ and CD141+ was demonstrated. DC subsets from BM clustered together and separate from the corresponding subsets from PB, which similarly formed a cluster. In BM, a common proliferating and immature differentiating state was observed for the two DC subsets, whereas DC from the PB showed a more immune-activated mature profile. In contrast, BM-derived slan+ non-classical monocytes were closely related to their PB counterparts and not to DC subsets, implying a homogenous prolife irrespective of anatomical localization. Additional functional tests confirmed these transcriptional findings. DC-like functions were prominently exhibited by PB DC. They surpassed BM DC in maturation capacity, cytokine production and induction of CD4+ and CD8+ T cell proliferation. This first study on myeloid DC in healthy human BM offers new information on steady-state DC biology and could potentially serve as a starting point for further research on these immune cells in healthy conditions as well as in diseases.